Brazilian clinical trial of uniform multidrug therapy for leprosy patients : the correlation between clinical disease types and adverse effects - Gonçalves, Heitor de Sá (2012)
This study sought to verify the correlation between leprosy types and the adverse effects of treatment drugs. This quantitative, prospective, nested study was developed at the Dona Libânia Dermatology Centre in Fortaleza, Brazil. Data were collected from November 2007-November 2008. During this period, 818 leprosy patients were diagnosed and began treatment. Forty patients with tuberculoid leprosy (TT) were selected. Twenty patients followed a standard therapy of dapsone and rifampicin and 20 were administered dapsone, rifampicin and clofazimine (U-MDT). Twenty patients with borderline lepromatous (BL) and lepromatous leprosy (LL) were also selected and treated with U-MDT. All of the subjects received six doses. With the exception of haemolytic anaemia, there was a low incidence of adverse effects in all the groups. We did not observe any differences in the incidence of haemolytic anaemia or other side effects across groups of patients with TT, BL or LL treated with U-MDT.